THE EFFECT OF OSHA, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE SATISFACTION AND EMPLOYEE PERFORMANCE - kunto, (Archives of Business Research, 2019)
ABSTRACT This study aims to analyze the effect of Occupational Safety and Health (OSHA), work environment and work discipline on job satisfaction and employee performance. The method used in this study is a survey conducted on the employees of PT. Maspion I Maxim Division of the Spray Coating Department. The sampling method uses saturated sampling, by taking the entire population of 70 employees to be respondents. The data used in this study are primary data. Data analysis and hypothesis testing in this study used Goodness of fit analysis in the Partial Least Square model. The results showed that the work environment and work discipline variables had a significant effect on employee performance while OSHA had no significant effect on employee performance. OSHA implementation and work discipline have a significant effect on job satisfaction. The environment has no significant effect on employee job satisfaction. Keywords : OSHA, work environment, work discipline, job satisfaction, employee performance